The Raison d'être of a Book: an Introduction to “International Criminal Law, Humanitarian Law and Refugee Law from the Perspective of Human Rights Law” - Béres, Nóra (International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law, 2026)
This chapter is meant to be an introduction to the volume of “International Criminal Law, Humanitarian Law and Refugee Law from the Perspective of Human Rights Law”, a piece of the textbook series designed for students of the Human Rights and Rule of Law LL.M. programme co-organised by the Central European Academy (Budapest, Hungary) and the Faculty of Law, University of Miskolc (Miskolc, Hungary). The paper briefly explains the interaction between international criminal law, humanitarian law, refugee law and human rights law, then determines the scope and aim of the book, dedicates the book to its target audience, explains why the book is unique among general international public law textbooks, and overviews a detailed structure of the book, including chapters on the history of international criminal law, on international crimes, on the International Criminal Tribunal for the Former Yugoslavia and on the International Criminal Tribunal for Rwanda, on the International Criminal Court, on the history of humanitarian law, on the principles of humanitarian law, on the 1949 Geneva Conventions and their Additional Protocols I-III, on the distinction and scope of migration law and refugee law in general terms, on the 1951 Convention Relating to the Status of Refugees, on the principle of non-refoulement, and on the special Central and Eastern European features of these fields. Finally, this chapter adds an acknowledgement as a closure of the editor’s introductory thoughts.Keywords: international criminal law, international human rights law, international humanitarian law, international public law, international refugee law